Use of Botanicals for Weevil Management: A Integrated Approach of Maize Weevil (Sitophilus zeamais) Management in A Storage Condition - Tiwari, S.; Thapa, R. B.; Sharma, S. (Journal of the Institute of Agriculture and Animal Science, 2018)
A study was conducted at Entomology Laboratory of Agriculture and Forestry University with the aim of evaluating the efficacy of potential plant materials to manage the maize weevil; Sitophilus zeamais Mots. (Coleoptera: Curculionidae) from April to October 2015. The mean temperature and RH of storeroom during the experiment period was 29.37°C and 71.91% RH. A completely randomized design (CRD) was laid out with three replicates. Seven plant materials such as Acorus calamus (rhizome powder) @ 10gm kg-1, Azadirachta indica (seed powder) @ 10gm kg-1, Artemisia vulgaris (leaf dust) @ 10gm kg-1, Zanthoxylum alatum (fruit powder) @ 4gm kg-1, Melia azadirach (seed powder) @ 10gm kg-1, Justicia adhatoda (leaf dust) @ 10gm kg-1 and control were used as treatments. After six months, the lowest percentage maize weight loss (1.5) and lowest grain damage (1.43%) was observed in Acorus calamus treated grains. However, the highest grain damage percentage (18.02%) and weight loss (57.30%) was recorded in control treatment. Similarly, the lowest number of exit holes (3.30) was observed in Acorus calamus treated grains but highest (47.00) were recorded in control. Significantly more numbers of weevil were emerged (57.00) in control treatment whereas only a few (2.70) were recorded in Acorus calamus treated grains. Hence, it is concluded that maize weevil showed less preference to Acorus calamus treated grains with minimum weight loss and less grain damage as compared to other botanicals. This finding is important for promoting locally available botanical materials to manage maize weevil in Nepal.